SiRA: a silicon rhodamine-binding aptamer for live-cell super-resolution RNA imaging - Wirth, Regina; Sünbül, Murat; Jäschke, Andres (Journal of the American Chemical Society, 2019)
Although genetically encoded light-up RNA aptamers have become promising tools for visualizing and tracking RNAs in living cells, aptamer/ligand pairs that emit in the far-red and near-infrared (NIR) regions are still rare. In this work, we developed a light-up RNA aptamer that binds silicon rhodamines (SiRs). SiRs are photostable, NIR-emitting fluorophores that change their open-closed equilibrium between the noncolored spirolactone and the fluorescent zwitterion in response to their environment. This property is responsible for their high cell permeability and fluorogenic behavior. Aptamers binding to SiR were in vitro selected from a combinatorial RNA library. Sequencing, bioinformatic analysis, truncation, and mutational studies revealed a 50-nucleotide minimal aptamer, SiRA, which binds with nanomolar affinity to the target SiR. In addition to silicon rhodamines, SiRA binds structurally related rhodamines and carborhodamines, making it a versatile tool spanning the far-red region of the spectrum. Photophysical characterization showed that SiRA is remarkably resistant to photobleaching and constitutes the brightest far-red light-up aptamer system known to date owing to its favorable features: a fluorescence quantum yield of 0.98 and an extinction coefficient of 86000 M-1cm-1. Using the SiRA system, we visualized the expression of RNAs in bacteria in no-wash live-cell imaging experiments and also report stimulated emission depletion (STED) super-resolution microscopy images of aptamer-based, fluorescently labeled mRNA in live cells. This work represents, to our knowledge, the first application of the popular SiR dyes and of intramolecular spirocyclization as a means of background reduction in the field of aptamer-based RNA imaging. We anticipate a high potential for this novel RNA labeling tool to address biological questions.